Vancomycin pharmacokinetics and dosing in critically ill adult patients on continuous renal replacement therapy: A scoping review - Maha S Assadoon; Jeffrey C Pearson; Shayma H Alzaidi (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose Acute kidney injury is common in critically ill patients, frequently requiring the use of continuous renal replacement therapy (CRRT). Both critical illness and CRRT significantly alter vancomycin pharmacokinetics, affecting dosing and therapeutic drug monitoring. This scoping review aimed to evaluate vancomycin pharmacokinetics and dosing in critically ill adults receiving CRRT. Summary A systematic scoping review was conducted using PRISMA-ScR guidelines. Studies published through April 2026 were identified using a comprehensive search of Ovid MEDLINE via PubMed, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov. Included studies were in English, involved critically ill adult patients on CRRT, and assessed vancomycin pharmacokinetics and dosing using single- or multiple-dose population pharmacokinetics. Authors screened studies using a standard form, and disagreements were resolved through consensus. The searches retrieved 114 studies, and 24 were included. Vancomycin total clearance (CL) ranged from 1.5 to 4.8 L/h and was consistently influenced by CRRT. CRRT accounted for at least 50% of total CL, with CRRT modality and intensity being key determinants. Vancomycin’s volume of distribution varied within a range of 0.4 to 1.4 L/kg. Population pharmacokinetic studies showed high interindividual variability, and dose simulation studies supported model-informed precision dosing. Simulation studies reported loading and maintenance dose ranges of 15-30 mg/kg and 5-20 mg/kg daily, respectively. Conclusion Vancomycin dosing in patients on CRRT is highly variable due to significant pharmacokinetic alterations, emphasizing the need for individualized dosing, therapeutic drug monitoring, and model-informed approaches. Future studies should focus on validating personalized dosing strategies and linking pharmacokinetic/pharmacodynamic targets with clinical outcomes in this population.